(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
The relationship between psychical reality and psychical reality under an aesthetic form is analyzed in this paper. Our psychical reality works in images and these images can be studied only from images, in the poetry of dreams. Starting from Gaston Bachelard’s poetics, the proposal of this paper is to comment the relationship between symbolic reality and the materiality of the world.